A Novel Bunyavirus-Like Virus of Trypanosomatid Protist Parasites - Akopyants, Natalia S; Lye, Lon-Fye; Dobson, Deborah E; Lukeš, Julius; Beverley, Stephen M (Genome announcements, 2016)
We report here the sequences for all three segments of a novel RNA virus (LepmorLBV1) from the insect trypanosomatid parasite Leptomonas moramango This virus belongs to a newly discovered group of bunyavirus-like elements termed Leishbunyaviruses (LBV), the first discovered from protists related to arboviruses infecting humans.